2010
DOI: 10.1111/j.1551-2916.2010.03763.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathode–Electrolyte Interfaces with CGO Barrier Layers in SOFC

Abstract: Electron microscopy characterization across the cathode–electrolyte interface of two different types of intermediate temperature solid oxide fuel cells (IT‐SOFC) is performed to understand the origin of the cell performance disparity. One IT‐SOFC cell had a sprayed‐cosintered Ce0.90Gd0.01O1.95 (CGO10) barrier layer, the other had a barrier layer deposited by pulsed laser deposition (PLD) CGO10. Scanning electron microscopy, transmission electron microscopy (TEM), and electron backscattered diffraction (EBSD) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
104
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 19 publications
8
104
2
1
Order By: Relevance
“…These findings correspond with earlier reports as grain boundary diffusion of Sr in Gd 0.2 Ce 0.8 O 1.9 has been found to be 10 5 times larger than the bulk diffusion and both calculations and experiments has shown grain boundaries as the dominant route for Sr diffusion. [24,27,28] figure 5b forming in the YSZ-CGO interface at the grain boundaries and spreading out along the interface. In figure 4 the density of these grains over the LSCF substrate is so high that when they elongate along the YSZ-CGO interface they come into contact and form a large continuous layer.…”
Section: Variation Of Cgo Barrier Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings correspond with earlier reports as grain boundary diffusion of Sr in Gd 0.2 Ce 0.8 O 1.9 has been found to be 10 5 times larger than the bulk diffusion and both calculations and experiments has shown grain boundaries as the dominant route for Sr diffusion. [24,27,28] figure 5b forming in the YSZ-CGO interface at the grain boundaries and spreading out along the interface. In figure 4 the density of these grains over the LSCF substrate is so high that when they elongate along the YSZ-CGO interface they come into contact and form a large continuous layer.…”
Section: Variation Of Cgo Barrier Thicknessmentioning
confidence: 99%
“…[21][22][23] An alternative way to fabricate CGO barriers are by physical vapor deposition techniques such as magnetron sputtering, pulsed laser ablation, and electron beam evaporation. [16,20,24] Studies comparing deposition techniques have provided evidence that CGO barrier layers fabricated by reactive magnetron sputtering show better performance. [16,25] This may be associated with higher density of such layers reached at lower temperatures than by wet ceramic deposition techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interlayer cannot completely eliminate SrZrO 3 formation, and the SrZrO 3 is often formed near the ceria/zirconia interface. [5][6][7][8][9][10][11][12][13][14] The amount and distribution of SrZrO 3 formation depends on the heat-treatment temperature of the interlayer. Wankmüller et al reported the influence of the sintering temperature of GDC interlayer on the morphology of SrZrO 3 formation.…”
mentioning
confidence: 99%
“…12,13 Such dispersed SrZrO 3 formation in the GDC interlayer have also been observed by other researchers. [7][8][9][10][11][12][13][14] However, the formation mechanism of such morphology, i.e. why SrZrO 3 formed dispersedly while maintaining the ionic conduction path for oxygen ion, is not yet clear.…”
mentioning
confidence: 99%
“…However, it has been reported that in some cases Sr can move through ceriabased electrolyte barrier layer and thus influence noticeably SOFC performance. 27,30,31 Sr mobility inside SDC phase is not widely investigated and more detailed investigation is needed. * Electrochemical Society Member.…”
mentioning
confidence: 99%